2021
DOI: 10.1002/tox.23424
|View full text |Cite
|
Sign up to set email alerts
|

Melamine induced changes in histopathology of the main organs and transcriptional levels of MAPK signaling genes in kidneys of female mice

Abstract: Melamine is an important chemical raw material used in industries, which has potential health risks to animals and humans. Current research mainly focuses on the toxic effects of high‐dose melamine ingestion. However, there are few reports on whether melamine at the current limited standard dose has adverse effects on various tissues and organs, and whether there are sensitive target genes for risk evaluation. For this, 24 female Kunming mice were fed 0, 1.8‐, 3.6‐, and 7.2‐ mg/kg/d melamine via drinking water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
0
5
1
Order By: Relevance
“…Here we have chosen IR‐induced and LPS‐induced AKI as our research models, since they could well represent two common clinical situations, ischemic organ injury and sepsis. As for the cell signaling pathways underlying AKI, multiple key pathway mediators including Nrf2, MAPK, NLRP3, and NF‐κB have been reported in ischemic injury, nephrotoxic agent‐induced AKI, and LPS‐induced AKI 27,29–31,33–35 . In the current study, however, we revealed the pivotal role of autophagy in IR‐induced and LPS‐induced AKI.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Here we have chosen IR‐induced and LPS‐induced AKI as our research models, since they could well represent two common clinical situations, ischemic organ injury and sepsis. As for the cell signaling pathways underlying AKI, multiple key pathway mediators including Nrf2, MAPK, NLRP3, and NF‐κB have been reported in ischemic injury, nephrotoxic agent‐induced AKI, and LPS‐induced AKI 27,29–31,33–35 . In the current study, however, we revealed the pivotal role of autophagy in IR‐induced and LPS‐induced AKI.…”
Section: Discussioncontrasting
confidence: 55%
“…As for the cell signaling pathways underlying AKI, multiple key pathway mediators including Nrf2, MAPK, NLRP3, and NF-κB have been reported in ischemic injury, nephrotoxic agentinduced AKI, and LPS-induced AKI. 27,[29][30][31][33][34][35] In the current study, however, we revealed the pivotal role of autophagy in IR-induced and LPS-induced AKI.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…ML is a common pollutant and carcinogen that threatens human and animal health, and has sparked major global concerns [ 29 ]. It is widely dispersed in the environment including water and soil [ 30 ], and has been incriminated as a substance in food adulteration [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely dispersed in the environment including water and soil [ 30 ], and has been incriminated as a substance in food adulteration [ 31 ]. The liver is the primary organ for metabolism and detoxification and one of the organs most seriously affected by ML exposure [ 10 , 29 ].…”
Section: Discussionmentioning
confidence: 99%